A Search of COVID-19 main Protease Inhibitor from Plant Derived Alkaloids using Chloroquine and Hydroxychloroquine as Reference: An In-silico Approach - Kolita, Bhaskor; Bora, Amlan Jyoti; Hazarika, Pinaki (International Journal of Scientific Research in Biological Sciences, 2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease that causes respiratory illness in human and has now become a major challenge for all over the world. As no drug is approved yet for COVID-19, it is strongly demanding to search lead compounds. Therefore, the current investigation is an attempt to screen lead molecule for inhibition of Covid-19 main protease. Herein, we considered 98 plant derived alkaloids having antimalarial activity, quinine and docked with COVID-19 main protease taking Chloroquine, hydroxychloroquine as reference. Finally, compounds Bidebiline E, Bisnordihydrotoxiferine and Thalifaberine were screened as lead molecule on the basis of Moldock score, H-bond interaction and ADMET study, and recommended for in vitro investigation.